Early operative outcome of pericardiectomy for symptomatic chronic tuberculous constrictive pericarditis - Jan, Azam; Muhammad Imran; Kunwar Muhammad Aqeel; Khan, Muhammad Tariq; Sumreen Begum; Mohammad, Amir; Shah, Syed Mumtaz; Ali, Imran (International Journal of Endorsing Health Science Research, 2019)
Background: Pericardiectomy procedure is commonly indicated for constrictive pericarditis (CP). One of the most important clue to diagnosis of CP is the signs and symptoms of right-sided heart failure that are not completely explained by presence of pulmonary disease or left-ventricular failure. The aim of this study was to assess clinical data presentation and early operative outcomes of pericardiectomy performed for symptomatic chronic constrictive pericarditis who had failed maximal medical therapy. Methodology: A retrospective analysis was carried out of consecutive constrictive pericarditis adult age patients who underwent pericardiectomy procedure from 2002 to 2012. The patients who had intraoperative diagnosis of other then constrictive pericarditis were excluded from further analysis. A total 51 patients were selected for this study. The preoperative assessment, intraoperative findings and postoperative course and outcome such as hospital stay, prolonge ICU stay, post-operative CPV etc. were evaluated. Results: 43 males and 8 females were include in the study among them 41% gave history of previous (TB) and 35% were pediatric patients (teens, as shown less than 19 years). 8 patients had effusive type pericarditis. The preoperative findings revealed dyspnea 54%, Chest Pain 45% and persistent cough 31%. Furthermore, 43% patients had ascites and 41% with pleural effusion. The mean preoperative central venous pressure (CVP) was 20.5 respectively. The post-operative outcome was short hospital stay, the post-operative patients CVP was estimated 13.5 and the mean drop of CVP due to pericardiectomy was estimated 7 respectively. Conclusion: The conclusive findings of our study revealed that among the patients of symptomatic chronic tuberculous CP, the timely pericardiectomy attempt can effectively improve the hemodynamics of the patient. The early pericardiectomy can also reduce the morbidity and mortality rate of these patients.